Introduced and native species on rocky shore macroalgal assemblages: zonation patterns, composition and diversity - Raffo, María Paula (2014)
The study of the natural and anthropogenic changes in patterns of species and habitat diversity is impor- tant for understanding the organization of natural species assemblages. One of the major threats to native marine biodiversity and resource values is the introduction of exotic species. Rocky intertidal shores are considered among the environments that are susceptible to the introduction of organisms like macroalgae. The scope of this work is to study the spatial variation of the native and introduced intertidal macroalgae in rocky shores of northern Patagonia, Argentina. Seasonal sampling of cover, abundance, richness, biomass and diversity of native and introduced macroalgae at three intertidal levels (high, middle and low) was carried out at four wave-protected rocky shores during one year. We found a con- spicuous zonation pattern of the dominant species of algae and invertebrates, with the greatest richness, abundance and algal diversity at the low intertidal level, but these variables were heterogeneous through time and space. These differences were mainly due to the variations in the abundance of ephemeral algae. Introduced species represented around 20–25% of the total richness of each locality, being most abun- dant in those localities that also showed a greater total diversity. This study provides the first assessment of rocky shore macroalgae assemblages from Argentina that incorporates the presence of introduced species and shows that the number of introduced algae species along Patagonian rocky shores had been underestimated. We also encourage the monitoring of the biodiversity and the study of the processes that are involved in the role that introduced species plays in these environments.